Yosef ben Mordekhay Malinowski: On the date of his death - Muchowski, Piotr; Yariv, Arie (Karaite Archives, 2014)
According to Jacob Mann, Yosef ben Mordekhay Malinowski, the prominent pupil of Yiṣḥaq ben Avraham of Troki, died after 1624. This article quotes some new data on the date of his death and proves it should be established within a few years after 1603. It points out that most probably Malinowski left Troki and moved to Łuck in 1602. The article also gives his brief genealogy and a list of his works.